BEHAVIORIST-BASED ARABIC CALLIGRAPHY INSTRUCTION IN DEVELOPING MORAL VALUES AMONG ARABIC LANGUAGE EDUCATION STUDENTS AT UNZAH GENGGONG PROBOLINGGO - Ahmad Zainullah; Uril Bahruddin; Danial Hilmi (Al-Muyassar: Journal of Arabic Education, 2026)
This study aims to (1) to explain Arabic calligraphy instruction using a behaviorist approach among students in the Arabic Language Education Department at Zainul Hasan Genggong Islamic University in Probolinggo, (2) to describe its contribution to the development of students’ moral values, and (3) to identify the challenges faced in its implementation. This study employs a qualitative approach to collect data in the field. It is a case study. The data collection methods used include observation, interviews, and document analysis. The data analysis method used in this study is the qualitative approach according to Miles, Huberman, and Saldana, which consists of data reduction, data presentation, and drawing conclusions. This study employs source triangulation and methodological triangulation. The results of the study conducted on Arabic Language Education students at Zainul Hasan Genggong Islamic University in Probolinggo are as follows: 1) Khat Araby instruction is carried out systematically using a behaviorist approach through structured practice, habituation, and reinforcement. Instructors provide examples, followed by repeated practice with guidance, immediate correction, and evaluations that emphasize both process and outcomes, thereby effectively improving students’ ability to write Arabic letters correctly and neatly. 2) Khat Araby instruction using a behaviorist approach makes a tangible contribution to the development of students’ moral values through repeated practice, immediate correction, and consistent reinforcement. This process not only improves writing skills but also fosters patience, discipline, perseverance, and responsibility. 3). The challenges faced include internal factors, such as low motivation, boredom, lack of self-confidence, and inconsistent practice, as well as external factors such as limited credit hours, facilities, classroom conditions, and the influence of digital technology. Behaviorist-based instruction in Khat Araby, utilizing structured practice and systematic reinforcement, has proven effective in improving students’ technical skills. These findings indicate that repetitive practice not only hones motor skills but also serves as a means of fostering moral values such as patience, discipline, perseverance, and responsibility.